A new subspecies of Grammosciadium macrodon Boiss. (Apiaceae) from Turkey - Bani, Baris; Koch, Marcus A. (Magnolia Press, 2015)
Grammosciadium macrodon subsp. nezaketae is described as endemic to Eastern Anatolia. The new subspecies differs remarkably from the G. macrodon subsp. macrodon based on fruit characters. In addition to the diagnostic fruit characters, other significant morphological and anatomical differences between these two taxa are presented as well. A quantitative, morphometric analysis was carried out to achieve more reasonable results and to discuss diagnostic characters in Grammosciadium macrodon and its morphologically closest relatives.
Keywords: 15. Life on land; 3. Good health